Sistem Pemilihan Umum dan Otoriternya Partai Politik Indonesia - Lalu Subandari (At-Tanwir Law Review, 2022)
The general election system in Indonesia adheres to a one-man-one-vote system, where everyone has one vote, regardless of educational background and social status. From the point of view of Indonesia's current education which is still not evenly distributed, as well as the social gaps that are still far away, causing the distribution of information and technology to be uneven, this causes uneven political maturity, in addition to Indonesia's geographical conditions adding challenges to the realization of justice in terms of education and Therefore, it is necessary to try the electoral college electoral system, reforms in the general election must also be in accordance with the improvement in the supervision of political parties which seem undemocratic in their implementation.